Xi yuan lu xiang yi : si juan, juan shou yi juan : Zhi yi, Zhi yi bu fu : Zhi yi, Zhi yi bu fu - Xu, Lian, 1787-1862.; Pan, Wei, 1816-1894; Ge, Yuanxu. er juan.; Zhang, Kailian. yi juan.; Hubei Sheng (China). Guan shu chu; Chinese Rare Book Collection (Library of Congress). ([Wuchang?] : Hubei Guan shu chu, 1890)
Detailed commentary on the Records of redressing injustice by Song Ci; originally published in the 4th year of Xianfeng, 1854; reprinted by Pan Wei dated 1877; this edition dated the 16th year of Guangxu, 1890.
In case.
Also available in digital form on the Library of Congress Web site.
Keywords: Song, Ci, -- 1186-1249.; Forensic pathology -- China; Coroners -- China